Using a top predator as a sentinel for environmental contamination with pathogenic bacteria: the Iberian wolf and leptospires - Millán, Javier; Oleaga, Álvaro; López-Bao, José V.; Candela, Mónica G.; Rodríguez, Alejandro; León-Vizcaíno, Luis (Memórias do Instituto Oswaldo Cruz, 2014)
et al. The Iberian wolf (Canis lupus) is the top predator in the Iberian environments in which it lives, feeding on a wide range of species, thus encountering a wide range of disease agents. Therefore, the wolf can serve as sentinel of environmental contamination with pathogens. We investigated the exposure of free-living wolves to 14 serovars of Leptospira interrogans sensu lato. Kidney samples from 49 wolves collected from 2010-2013 in northwestern Spain were analysed by culture, direct immunofluorescence and polymerase chain reaction. Tissue fluids were analysed for antibodies by a microscopic agglutination test. Ten wolves (observed prevalence: 20%, 95% confidence interval = 11-33%) showed evidence of contact with leptospires, eight through direct detection and nine through serology (7 wolves were positive according to both techniques). Titres below the cut-off level were also detected in seven cases. Serovars confirmed were Canicola (n = 4), Icterohaemorrhagiae (n = 3) and Sejroë, Ballum and Grippotyphosa (n = 1 each), indicating that wolves were infected with serovars for which dogs, rodents and ungulates, are the natural hosts and supporting the utility of the wolf and other large predators as environmental sentinels for pathogens. The agreement between CSIC and Principado de Asturias. Peer reviewed